STAR WARS. - Giovannetti-Singh, Gianamar (History Today, 2025)
The article examines the debate surrounding the antiquity of Chinese civilization, particularly through the lens of 18th-century European perspectives, focusing on the contrasting views of Anglican vicar George Costard and Jesuit astronomers like Antoine Gaubil. While Jesuit missionaries argued for China's ancient history based on astronomical records, Costard vehemently rejected these claims, labeling them as fictitious and politically motivated. He criticized the reliance on Chinese celestial observations, linking their credibility to the despotic nature of the Chinese government, which he believed compromised the integrity of historical records. This discourse reflects broader tensions between European Enlightenment ideals and the political implications of knowledge production in both China and Europe.